ESTUDIO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UN CENTRO GERONTOLÓGICO EN LA CIUDAD DE LOJA - Vivanco Ochoa, Johanna Vanessa (2016)
Elderly care in our country is very scarce. Few government entities that exist, provide a poor service and does not meet the needs of this sector. There are very few centers or nursing homes, many of whom in very poor and unfavorable way to cater to a small group of senior citizens in regard to the city of Loja. Is why this thesis aims general: "make a study of feasibility for the implementation of a gerontological Centre in the city of Loja", in which is to deliver comprehensive care, tranquility and entertainment so they can interact and do not feel isolated and unproductive. In relation to the specific objectives proposed: "conduct four studies containing an investment project, so we have: market study, technical, financial study and financial evaluation". In order to meet the objectives set were used the following methods and techniques, so we have: the method of inductive, deductive, and analitico-sintetico. Among the techniques was applied direct observation, interviews and surveys in order to extract the information needed to carry out the investigative work. In the results was the tabulation of the interviews and surveys using mathematical techniques and statistics; all these data will help to determine the situation in which the company; lies and at the same time help to make proposals, which will allow the company to improve service and thus achieve higher profits. Then it is the discussion where the four studies was developed, so we have: was established in the study of market supply and demand of service that will be provided in the gerontology Center, and therefore also the existing unsatisfied demand; In addition to indicate the services that provide the gerontology Center "New life". The technical study determined fundamentals of engineering of the project, the size, the location of the Center and established optimum and strategic location of the Center to the city of Loja, urban area. As regards the organizational study determined the kind of society that will be implemented through the organizational structures and functions manuals. The financial study presents a budget that determines the initial investment for the implementation of the project, which is $201.558,33, which was funded by 50% by the partners, while the other 50% of difference by a credit to the Banco National de Foment. In the financial assessment, through the analysis of economic indicators could determine the viability of the project. Where was obtained the following results: the VAN project is of $165.115,96 $ demonstrating the feasibility of the implementation of the same, then the IRR is 22.77% higher than the opportunity cost of capital, the benefit that the company will obtain is 49 cents for each dollar invested, also it was found that the company regains the capital invested in 6 years , 0 months and 26 days and finally the sensitivity analysis supports an increase of 11.62% in costs and a decrease of 8.02% in revenues, which means that the project does not suffer any sensitivity to possible changes. And finally, as regards the conclusions is considered the creation of a professional private gerontological Centre has a favorable reception; as a result also allowed to develop relevant recommendations. It should be noted that this work contributes to the readers, most of them students and professors, critico-reflexivos elements that allow us to know our reality.